A STUDY ON FACTORS INFLUENCING THE PURCHASE OF ELECTRIC VEHICLES IN INDIAN AUTO MOBILE MARKET - Prof. Rajesh,; Dr. Rajasulochana,; Dr. M. Kethan, (The journal of contemporary issues in business and government, 2022)
The EV space has getting Hotter day by day with more and more legacy where all the Big Car manufacturing giants are making entry. Pollution has become a major source of concern for the majority of people at present. Everybody wants to live in a pollution-free society, Pollution is primarily caused by automobiles Nevertheless, and India’s automobile registrations are growing at a rapid pace, Petrol and diesel process are also soring high As a result, and modes of transportation started becoming more sustainable and environmentally friendly. This made the electric vehicles to create a space but the adoption rate was not more in India, projections by many manufactures are expected in next 5-6 years, this study includes five independent variables: financial incentives, charging infrastructure, social reinforcement, environmental concern, and price, and one dependent variable, electrical vehicle adoption. The data for the present study was collected from 150 randomly selected respondents across India, Confirmatory Factor Analysis (CFA) were used to analyze the data. The study’s findings demonstrate that pricing has a substantial impact on the adoption of electric vehicle.